Risk of Occupational Burnout among South African Working Parents of Children with Autism Spectrum Disorder - Lukeso Kuyokila Patience (Canadian Journal of Business, Economics and Health Management, 2026)
This study investigated the effect of parenting children with autism on occupational burnout among working parents of children with autism. The aim of the study was to determine the extent to which parents raising children within autism spectrum disorder are predisposed to emotional exhaustion, cynicism or depersonalisation from their work tasks, and decrease of professional efficiency. A quantitative methodology was employed to collect and analyse data from a sample of 182 working parents of children with autism by means of the Oldenburg-burnout Inventory (OLBI) and Parenting Daily Hassles Scale (PDH). The research results revealed a positive correlation between working while parenting children with autism and all the dimensions of occupational burnout (exhaustion and work disengagement). The research results have managerial, legal, and labour relations implications for organisations employing parents of children with autism. Recommendations are formulated to create a working environment that alleviates the psychological burden of parents raising children within autism spectrum and improve their well-being.